1994
DOI: 10.1172/jci117603
|View full text |Cite
|
Sign up to set email alerts
|

Variation at the hepatic lipase and apolipoprotein AI/CIII/AIV loci is a major cause of genetically determined variation in plasma HDL cholesterol levels.

Abstract: Genetic factors have been shown to play an important role in determining interindividual variation in plasma HDL-C levels, but the specific genetic determinants of HDL cholesterol (HDL-C) levels have not been elucidated. In this study, the effects of variation in the genomic regions encoding hepatic lipase, apolipoprotein AI/CIII/AIV, and the cholesteryl ester transfer protein on plasma HDL-C levels were examined in 73 normotriglyceridemic, Caucasian nuclear families. Genetic factors accounted for 56.5±13% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
100
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(102 citation statements)
references
References 55 publications
1
100
0
1
Order By: Relevance
“…2 7, 2 8 The critical role of leptin's actions directly in the CNS have been established with the findings that a brain-specific knockout of the leptin receptor causes obesity similar to that of db/db mice and brainspecific expression of a LepRb transgene can suppress the obesity of db mice. 29,30 In aggregate, these data established that leptin is a novel hormonal signal in a negative feedback loop that maintains homeostatic control of adipose tissue mass by modulating the activity of neural circuits that regulate food intake, energy expenditure and metabolism. These conclusions are important not only because key elements of the homeostatic system regulating weight were identified but also because the identification of leptin and its receptor confirmed the very existence of a homeostatic system that many believed did not exist at all.…”
Section: The Cloning Of the Ob Gene And Identification Of Leptin Has mentioning
confidence: 98%
“…2 7, 2 8 The critical role of leptin's actions directly in the CNS have been established with the findings that a brain-specific knockout of the leptin receptor causes obesity similar to that of db/db mice and brainspecific expression of a LepRb transgene can suppress the obesity of db mice. 29,30 In aggregate, these data established that leptin is a novel hormonal signal in a negative feedback loop that maintains homeostatic control of adipose tissue mass by modulating the activity of neural circuits that regulate food intake, energy expenditure and metabolism. These conclusions are important not only because key elements of the homeostatic system regulating weight were identified but also because the identification of leptin and its receptor confirmed the very existence of a homeostatic system that many believed did not exist at all.…”
Section: The Cloning Of the Ob Gene And Identification Of Leptin Has mentioning
confidence: 98%
“…Forty to sixty percent of the variation in HDL levels appear to be genetic, 25 and Cohen et al have demonstrated genetic linkage between the hepatic lipase promoter (LIPC) locus and HDL-C levels that account for approximately 25% of the interindividual variation in plasma HDL-C levels. 26 HL activity appears to be influenced by several different factors including intra-abdominal fat (IAF), 27 ethnic background, 28,29 sex-steroid hormones, 30 -32 and LIPC genotype. 28,29 Four polymorphisms have now been identified in the 5Ј flanking region of the LIPC gene; a G to A substitution at position Ϫ250, C to T at Ϫ514, T to C at Ϫ710, and A to G at Ϫ763, which appear to be in complete linkage disequilibrium in white populations.…”
Section: H Epatic Lipase (Hl) Is a 476 Amino Acid Glycoproteinmentioning
confidence: 99%
“…In the promoter, cis-acting negative elements and hepatocyte nuclear factor binding sites were found (HadzopoulouCladaras and Cardot 1993;Oka et al 1996;Chang et al 1997). Cohen et al (1994) initially reported that HL gene variation determined HDL-C levels in Caucasian families, and subsequently found that nucleotide diversity and the haplotype of the HL promoter was associated with low HL activity and high HDL-C levels in Caucasians (Guerra et al 1997). Interestingly, the Ϫ514T allele, which is associated with low HL activity (70%-80% of normal), is more frequent in African Americans than in Caucasians Nie et al 1998).…”
Section: Introductionmentioning
confidence: 99%